Chemo- and bio-informatics insight into anti-cholinesterase potentials of berries and leaves of Myrtus communis L., Myrtaceae: an in vitro/in silico study - Baydaa Abed Hussein; Isaac Karimi; Namdar Yousofvand (BMC, 2023)
Abstract Background Myrtus communis L. (MC) has been used in Mesopotamian medicine. Here, the cholinesterase (ChE) inhibitory potential of its methyl alcohol extracts has been investigated and computationally dissected. Method The ChE inhibition has been measured based on usual Ellman's colorimetric method compared to a canonical ChE inhibitor, eserine. Through a deep text mining, the structures of phytocompounds (= ligands) of MC were curated from ChemSpider, PubChem, and ZINC databases and docked into protein targets, AChE (PDB 1EVE) and BChE (PDB 1P0I) after initial in silico preparedness and binding affinity (BA; kcal/mol) reported as an endpoint. The calculation of ADMET (absorption, distribution, metabolism, excretion, and toxicity) features of phytocompounds were retrieved from SwissADME ( http://www.swissadme.ch/ ) and admetSAR software to predict the drug-likeness or lead-likeness fitness. The Toxtree v2.5.1, software platforms ( http://toxtree.sourceforge.net/ ) have been used to predict the class of toxicity of phytocompounds. The STITCH platform ( http://stitch.embl.de ) has been employed to predict ChE-chemicals interactions. Results The possible inhibitory activities of AChE of extracts of leaves and berries were 37.33 and 70.00%, respectively as compared to that of eserine while inhibitory BChE activities of extracts of leaves and berries of MC were 19.00 and 50.67%, respectively as compared to that of eserine. Phytochemicals of MC had BA towards AChE ranging from -7.1 (carvacrol) to -9.9 (ellagic acid) kcal/mol. In this regard, alpha-bulnesene, (Z)-gamma-Bisabolene, and beta-bourbonene were top-listed low toxic binders of AChE, and (Z)-gamma-bisabolene was a more specific AChE binder. Alpha-cadinol, estragole, humulene epoxide II, (a)esculin, ellagic acid, patuletin, juniper camphor, linalyl anthranilate, and spathulenol were high class (Class III) toxic substances which among others, patuletin and alpha-cadinol were more specific AChE binders. Among intermediate class (Class II) toxic substances, beta-chamigrene was a more specific AChE binder while semimyrtucommulone and myrtucommulone A were more specific BChE binders. Conclusion In sum, the AChE binders derived from MC were categorized mostly as antiinsectants (e.g., patuletin and alpha-cardinal) due to their predicted toxic classes. It seems that structural amendment and stereoselective synthesis like adding sulphonate or sulphamate groups to these phytocompounds may make them more suitable candidates for considering in preclinical investigations of Alzheimer's disease.